The Transistion of Public Services at the Civil Registration Office (DISDUKCAPIL) of Pekanbaru City: case; public Services before, during, and pasca pandemic Covid-19 or new normal era - Yahya, MHD. Rafi; Anugerah, M Fajar; Hakim, Amri (Kemudi, 2024)
This research focuses on the evolution of public service delivery by Disdukcapil Pekanbaru City, with particular emphasis on the periods before, during and after the Covid-19 pandemic. The study aims to investigate and document the changes, challenges and adaptations in public service delivery over these different periods. Disdukcapil is one of the government agencies that is quite busy in providing services to the community. Referring to the data recorded on the official website of Disdukcapil Pekanbaru City in 2019, there were 30,402 services provided to the community. In 2020, Indonesia was hit by a Covid-19 pandemic that paralyzed the government. Many government agencies were unable to carry out their functions and provide services. Disdukcapil Pekanbaru City is one of the affected government agencies. While the government is making efforts to overcome or mitigate the spread of Covid-19 in the community, service matters certainly cannot stop. Therefore, the government must adapt and continue to carry out its functions to ensure that services are still provided to the community. To see how public services are provided, this research uses Peter John's policy implementation theory. This research uses qualitative research methods. The types and sources of data in this research are primary data and secondary data obtained using interviews and documentation, then analyzed qualitatively. The technique of determining informants using purposive sampling. This research aims to provide an overview of how changes in the implementation of public services in Disdukcapil Pekanbaru City.